Locoregional Flaps for Oral Cavity Reconstruction: A Review of Modern Options. (August 2017) - Patel, Urjeet A.; Hartig, Gregory K.; Hanasono, Matthew M.; Lin, Derrick T.; Richmon, Jeremy D.
Objective: To review state-of-the-art modifications and advances in soft tissue local and regional flap reconstruction of the oral cavity and to determine the role these techniques play in current practice. Data Sources: Review of the literature regarding oral cavity reconstruction. Review Methods: The authors describe advances in locoregional reconstructive options and assimilate data from the literature that compare recent advances to the historic standards. Conclusions: Modern advances in regional reconstruction of the oral cavity offer outstanding results and demonstrate potential advance over free tissue transfer. These modifications demonstrate the prominent role that regional reconstruction can play in oral cavity reconstruction. Implications for Practice: With a more complete understanding of these options, the surgeon is better able to tailor the reconstruction to the needs of the patient to provide high-quality cost-effective care.